Evaluasi Kebijakan Pemerintahan Daerah Provinsi Bengkulu Melalui Renja Tahun 2016-2021 dalam Peningkatan Pariwisata Studi Kasus Dinas Pariwisata Provinsi Bengkulu - Yohanes Susanto; Wita Hairani (STIA Bengkulu, 2024)
This research aims to evaluate the Regional Government Policy of Bengkulu Province for 2016-2021 through Renja to Improve Tourism. This research uses descriptive analysis methods. The data collection technique in this study uses the documentation method. The data used is secondary data sourced from books, literature, journals, reports and official information from state institutions as well as accessed via the internet. Based on research, it is known that the Bengkulu Provincial Government's policy in the work plan of the Bengkulu Province tourism office for 2016-2021, if we look at the progress each year through the planned programs, has been achieved and is right on target, even though there are also some programs that have not been achieved, overall they have been achieved very well. . In 2016-2017 the existing programs included increasing destination development, increasing ease of investment and professionalism of human resources, as well as increasing new creative economic actors in developing the creative economy, then in 2018-2019 the programs achieved were improvements to the follow-up program from the previous year including development tourism marketing, development of tourism products and services, development of tourist destinations and development of the creative economy, then in 2020-2021 we will know that the Indonesian nation, even on an international scale, is experiencing an outbreak of the Covid-19 virus, therefore the regional government of Bengkulu Province is focused on dealing with recovery from the impact of the Covid-19 pandemic.